Edukasi Cuci Tangan pada Anak Usia Dini di PAUD Bani Malik - AZ ZAHRA, FITRAH ANNISA; Handayani, Rahmaya Nova; setianingsih, sitti; A, M Aryadi; Suandika, Made; Agus, dwi (Jurnal Pengabdian Harapan Ibu (JPHI), 2025)
Early childhood is an important period in a child's development, where rapid growth occurs. At this stage, health behaviors, such as proper handwashing, are crucial for children to understand, given their low immune system. The purpose of this community service activity is to increase the knowledge of PAUD Bani Malik students about how to wash hands properly for early childhood. This activity was carried out on January 22, 2025 at PAUD Bani Malik, kembaran District, Banyumas Regency, involving 25 children. this activity is very important to increase understanding and change behavior, and implement a healthy lifestyle through proper hand washing habits. PAUD Bani Malik students enjoyed participating in the proper handwashing education because it was carried out by singing while learning and hands-on practice